Secret agents - Gilbert, Adrian (Laguna Hills, CA : QEB Pub., 2008)
Discusses American, British, and Russian spies and secret agents, and the history of espionage, with profiles of famous spies and double agents.
Includes index.
5.6
3-6
Keywords: Secret service -- Juvenile literature; Spies -- Juvenile literature; Secret service; Spies; Secret service; Spies; Secret service; Spies